Analisis Finansial Tambak Ikan Bandeng (Chanos chanos) di Desa Dualaus. Kecamatan Kakuluk Mesak. Kabupaten Belu - Mau, Antanika Sose; Sunadji, Sunadji; Dahoklory, Nicodemus (Jurnal Aquatik, 2024)
The research was conducted for one month. namely on June 1 - July 1. 2023. located in Dualaus Village pond. Kakuluk Mesak District. Belu Regency. The purpose of the study was to determine the characteristics of milkfish farmers and the level of feasibility of milkfish pond business financially carried out by farmers in Fatuketi Village. as well as how to overcome obstacles in milkfish farming business. In this research. the methods applied include the use of Observation and Interview methods as a way to obtain primary and secondary data at the research site. The collected data were then analyzed through Characteristic Analysis and Feasibility Analysis. The results obtained by the characteristics of respondents include most of the ages of 40-60 years as much as (60%). with an average elementary school education as much as (60%) and the characteristics of respondents based on business experience mostly 21-30 years as much as (60%) who have run a milkfish rearing business that can produce 1094.8kg in one cultivation. The milkfish farming business in Dualaus Village is considered feasible to continue based on the analysis of the average profit of 37.263.000 break event points (BEP) with details of BEP (Kg) 2.086.45 kg and and BEP (RP) Rp. 20.963.64 / kg and (R / C) = 2.67. While the obstacles faced in Dualaus Village include the lack of water supply in the dry season in cultivation activities and the lack of water quality measuring instruments. So the solution in dealing with this is to ensure that the water level is at the minimum limit during the dry season and does not exceed the maximum limit in the rainy season. and provides water quality measurement tools and pest and disease management. Keywords: Financial feasibility analysis. milkfish